Strategy of Vegetables Traders in Maintaining Social Capital with Workers - Riyanto, Sugeng; Ambayoen, Mas Ayu; Nala Mubarak, Ahmad Hilman (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.8, 2019)
East Java as one barometer of the economic development of Indonesia and has an important role in growing the economy of Indonesia. East Java is an Indonesian rice barns, so did the horticultural farm in East Java also do not want to fall behind the other regions, East Java has featured vegetable Sentara centres capable of supplying the needs of vegetable in East Java. The success of the East Java region became the centre of vegetables can not be separated from marketing activities of vegetable payments needs capital activities support the successful marketing of vegetables. This research activity will try exploring preservation form of social capital among vegetable traders and their workers. This study used a qualitative approach to the vegetable traders in the village Tawangargo. Qualitative approach in this research is conducted using research strategy CASE STUDY. The results of the study illustrate how social capital with traders keeping their workers are with; 1. Make workers as partners 2. Give decent salary and bonus 3. Comfort in work.